The Influence of Project-Based Learning Assisted by an Incubator Machine on Elementary Students’ Participation and Activeness at Sekolah Dasar Negeri 1 Teluk, Banyumas - Mohamad Januar; Wanda Nugroho Yanuarto (Proceedings Series on Social Sciences & Humanities, 2025)
The use of conventional methods has not yet implemented innovative learning models, and the learning media used are less attractive to students, making the learning process seem monotonous and boring. The Project-Based Learning (PjBL) method is expected to provide benefits as a solution to improve the quality of learning. PjBL assisted by an incubator machine aims to offer an alternative approach to teaching animal reproduction, particularly oviparous animals. Learning using the PjBL method can serve as a solution to create enjoyable classroom experiences, enhance curiosity, leave lasting impressions, and attract students’ interest to actively participate, thereby achieving the learning objectives. The steps taken in the implementation of PjBL included preparing essential questions about animal reproduction. How do oviparous animals (chickens) reproduce. Students observed this directly through the use of an incubator machine, rather than the traditional knowledge of natural incubation by a hen. Students were divided into groups and tasked with recording and monitoring the eggs for 21 days in the form of observation reports. There was an increase in student participation and activeness in learning from a score of 19 before using the incubator to 36 out of a maximum score of 40 after its use. This indicates that the PjBL method assisted by an incubator in the topic of oviparous animal reproduction can increase student participation and activeness.